Pengaruh Faktor Internal Rumah Tangga Terhadap Curahan Waktu Kerja Wanita Tani Kopi Arabika Di Kecamatan Atu Lintang Kabupaten Aceh Tengah - Cut Puteh Manyang; T. Fauzi; Irwan A. Kadir (Fakultas Pertanian, Universitas Syiah Kuala, 2022)
This study aims to determine 1) the allocation of working time for women farmers in household activities and Arabica coffee farming activities for 1 harvest season. 2) household internal factors that affect the working time of women Arabica coffee farmers during 1 harvest season. The sampling technique used is the Sample Random Sampling technique, namely random sampling, where each sample element has an equal opportunity to be selected as a sample. Determination of the number of samples using the Slovin method, the number of samples taken was 98 samples. The types of data used in this study are primary and secondary data. The analysis technique used is descriptive analysis and multiple linear regression analysis. The results showed that the average working time allocation for Arabica coffee farmers in household activities was 615 hours per harvest season, while the average working time for Arabica coffee farmers in Arabica coffee farming activities was 2,592 hours per harvest season. The results of the study can be concluded that the outpouring of working time for women farmers in household activities is lower than the time spent working in Arabica coffee farming activities. Based on the results of multiple linear regression analysis, the variables of age, education level, number of dependents in the family, land area, farming experience and employment status of women farmers have a significant effect on the working time of women Arabica coffee farmers. While the partial test (t-test) variables of age, land area and farming experience have a significant effect on the working time of women Arabica coffee farmers. Meanwhile, the variables of education level, number of family dependents and work status of women farmers did not significantly affect the working time of women Arabica coffee farmers.